2023
DOI: 10.1111/avj.13275
|View full text |Cite
|
Sign up to set email alerts
|

A review of thermal stress in cattle

RW Shephard,
SK Maloney

Abstract: Cattle control body temperature in a narrow range over varying climatic conditions. Endogenous body heat is generated by metabolism, digestion and activity. Radiation is the primary external source of heat transfer into the body of cattle. Cattle homeothermy uses behavioural and physiological controls to manage radiation, convection, conduction, and evaporative exchange of heat between the body and the environment, noting that evaporative mechanisms almost exclusively transfer body heat to the environment. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
(241 reference statements)
0
3
0
Order By: Relevance
“…As a result, when temperatures stray from this optimal range, it can impact calf behavior and physiology in various ways. These include increased energy expenditure to maintain warmth, decreased activity levels to minimize heat loss, the instinct to seek shelter, and the tendency to huddle together with other calves for warmth [ 64 , 65 ]. All those changes can potentially impact growth rates and overall health [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, when temperatures stray from this optimal range, it can impact calf behavior and physiology in various ways. These include increased energy expenditure to maintain warmth, decreased activity levels to minimize heat loss, the instinct to seek shelter, and the tendency to huddle together with other calves for warmth [ 64 , 65 ]. All those changes can potentially impact growth rates and overall health [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Releasing thyroid hormones from the hypothalamus promotes heat production by increasing the metabolic rate [1]. In cattle, environments with a −15 • C temperature increase metabolic activity by 35% due to their increasing thyroxine levels [53]. Moreover, mild hypothermia (35 • C) in rats increases their plasma levels of corticosterone and thyrotropin-releasing hormone while their prolactin levels decrease [54].…”
Section: Hypothalamus and Central Thermal Modulationmentioning
confidence: 99%
“…This interacted with the Health Domain, as cattle with BRDC may have impaired pulmonary capacity (97). Since cattle in high environmental temperatures thermoregulate via evaporative cooling (95), this may inhibit their ability to cool their body (98). The open-mouth breathing observed during the pen check (which was not observed in other steers in the pen) suggested that Physical Environment and Health Domains were impacted, and the associated mental effect of thermal discomfort, overheating, and breathlessness, which is considered a significant animal welfare issue (99), were impacting the steer's welfare.…”
Section: Case Study: Applying the Five Domains Modelmentioning
confidence: 99%